The thermo-mechanical response of PP nanocomposites at high graphene loading. Issue 3 (August 2015) - Yang, Kai; Endoh, Maya; Trojanowski, Rebecca; Ramasamy, Radha P.; Gentleman, Molly M.; Butcher, Thomas A.; Rafailovich, Miriam H.
<x content-type="archive" xml:space="preserve">Abstract</x> Authors have successfully fabricated polypropylene/graphene nanoplatelets (PP/GNPs), nanocomposites that are thermally conductive, processable, and flame resistant. Thermal conductivity measurements indicated that the thermal coefficient scaled linearly with GNP loading, where a value of 2.0 W m− 1 K− 1 was achieved at 40 wt-% loading. Tensile measurements indicated that the modulus increased linearly with GNP loading, while the Izod impact, after an initial decrease, remained constant for loadings up to 50 wt-%. Small angle X-ray scattering (SAXS) showed a large decrease in the amount of lamellar structure relative to the neat PP, while wide angle X-ray scattering (WAXS) showed a high degree of crystallinity. These results are consistent with formation of a new type of layered nanocomposite, composed of crystalline PP chains oriented onto layered GNPs.